(untitled) (JULACE: Journal of the University of Namibia Language Centre, 2022)
Abstract The paper offers a critique of the traumatic experience of the Namibian children during the liberation struggle as presented in “The Price of freedom” and “Walking the Boeing 707”. When Namibia gained independence in 1990, many Namibians came back home from exile and amongst them were children. The paper found that the memoirs, “The Price freedom” and “Walking the Boeing 707”, capture the traumatic experiences faced by the Namibian children while in exile and even upon returning home. The children of the liberation struggle grew up in children’s homes away from their biological parents. This rendered the Namibian children of the liberation struggle vulnerable as they were confronted with various problems such as dropping out of school, death, and grief with no psychosocial assistance. Moreover, the study adopted a qualitative literary research approach that examined the lives experience and traumatic events. The findings suggest that there is compelling evidence that many Namibian exiled children deserve to be recognized as heroes and heroines as they also contributed to the independence of Namibia. Children of the liberation struggle literally and figuratively placed their life and limb in harm’s way to liberate the country.